(untitled) (Ustozlar uchun, 2026)
This article focuses on the importance of Artifical intelligence in education. It explains how it help both teachers and students for orgazining productive and interactive lessons, get advice on difficult situations. This article also gives information about both positive and negative sides of AI in education. Furthermore, it emphasizes that AI should be used as a supportive tool rather than replacement for teachers.